The usage of the demonstrative pronoun šìtas, šità in some Eastern Aukštaitian subdialects - Judžentytė-Šinkūnienė, Gintarė (Baltistica, 2019)
The present paper aims to discover the reasons why ‘proximal’ demonstrative pronouns are used where ‘distal’ ones are expected. For the analysis, some Eastern Lithuanian subdialects (Obeliai, Juodupė, Jauneikiai, Stočkai) were chosen. In my research I have shown that physical proximity or distance from interlocutors is not the only determinant of using and selecting (nominal) exophoric demonstratives in some Eastern Lithuanian dialects; rather, these deictics are used according to the degree of access that the interactants, the addressee in particular, have to the referent.